Новый вид жука-скакуна (Coleoptera, Cicindelidae) из Северного Казахстана - Пучков, А.В. (Вестник зоологии, 1993)
Cicindela (Ciphalola) kutshumi sp. n.— Similar to C. deserticola, easily recognizible by longer upper lip, hind feet / leg ratio, shorter glans penis. Type locality: Akmolinsk distr., Basaga-ozek valley. Type material is deposited in Zoological Institute. Russian Academy of Sciences (St.-Petersburg) and in Institute of Zoologv, Ukrainian Academy of Sciences (Kiev).